Association of plasma BDNF and MMP-9 levels with mild cognitive impairment: a matched case-control study - Tingyu Zhang; Huili Si; Jiali Liao; Rulin Ma (Scientific Reports)
Abstract The prevalence of Alzheimer’s disease (AD) is on the rise globally, and everyone who develops AD eventually experiences mild cognitive impairment (MCI) first. Timely intervention at an early stage of the disease may mitigate disease progression. Recent studies indicate that BDNF and MMP-9 play a significant role in the pathogenesis of AD. Therefore, this study aims to ascertain whether there are differences in plasma BDNF and MMP-9 levels between individuals with mild cognitive impairment due to AD and those with normal cognition, and to analyze the factors influencing mild cognitive impairment.This case-control study included 102 individuals with mild cognitive impairment and 102 controls, matched by age and sex. Participants completed a series of questionnaires, neuropsychological assessments, and clinical examinations. Plasma concentrations of BDNF and MMP-9 of the participants were quantified using ELISA. Subsequently, the factors influencing MCI were analyzed using univariate and multivariate logistic regression. The differences in plasma BDNF levels, MOCA total scores, and scores in various cognitive domains (including visuospatial and executive abilities, abstract thinking, attention, language, naming, and delayed memory) between the MCI and the control groups showed statistically significant (p < 0.05). Logistic regression analysis revealed that plasma BDNF levels and years of formal education were significantly negatively associated with MCI. This study indicates that plasma BDNF and years of formal education are protective factors influencing cognitive function.